Studies on the Biology and Effect of Seasonal Variation on the Growth and Silk Production by Erisilk Worm Philosamia Bioini Hutt. - Sachan, J N; Bajpai, S P (Annals of Arid Zone, 2016)
The studies on the biology of Erisilk worm Philosamia ricini were undertaken, keeping in view to explore the possibility of its successful rearing in different months of the year in the semi-arid regions of Rajasthan where castor is grown abundantly with a little irrigation. Studies were conducted on local castor variety and was found that total life cycle of Erisilk worm is about 46, 59 and 88 days in first second and third generation respectively. During August-September the mean temperature 27.34°C± 5°C and humidity 78% ± )0 were found most favourable for larval growth, weight of cocoon and in shortening the duration of life cycle. Where as the period February to April when mean temperature 1430e ± SOC and humidity 38.7% ± 10 were found unfavourable. Present studies have proved that farmers can take the rearing of castor silk worm in the region successfully, except in the summer months.